A study on how Klang Port Management Sdn. Bhd. can be fully utilized in promoting international trade / Norhisham Bakar - Bakar, Norhisham (1999)
Lack of customers may cause many disbenefits not only to Klang Port Management Sdn. Bhd. (KPM) as a port management but also to overall logistics chain such as freight forwarding agents, haulage companies, shipowners, and also warehousing companies. In general, it will also affect the national economy. The purpose of this research is to analyze and to stress on the important of the utilization of Klang Port Management Sdn. Bhd. in promoting international trade. The utilization of KPM is important to ensure maximum results and to eliminate any difficulties to encourage more cargo owners using local port. KPM also must aware the situation and find out the solution to overcome this problems. As the largest port in Malaysia, KPM should attract more customers to use their port. Services provided by KPM, which includes efficient transport facilities and current facilities and development must be fully utilized by Malaysian cargo owners. The location of KPM in the Free Commercial Zone also one of the advantages to the cargo owners to utilize KPM. Cargo owners must aware that they should do much to change their attitudes towards Malaysian port. At the end of the study, the researcher provides some recommendations to the problems. KPM can use the recommendations as a guideline in order to reduce or solve the problems.